Random cellulose acetate nanofibers: a breakthrough for cultivated meat production - Santos, Ana Elisa Antunes dos; Guadalupe, Jorge Luís; Albergaria, Juliano Douglas Silva; Almeida, Itallo Augusto; Moreira, Amanda Maria Siqueira; Copola, Aline Gonçalves Lio; Araújo, Isabella Paula de; de Paula, Ana Maria; Neves, Bernardo Ruegger Almeida; Santos, João Paulo Ferreira; da Silva, Aline Bruna; Jorge, Erika Cristina; et al. (Frontiers in Nutrition, 2024)
Overcoming the challenge of creating thick, tissue-resembling muscle constructs is paramount in the field of cultivated meat production. This study investigates the remarkable potential of random cellulose acetate nanofibers (CAN) as a transformative scaffold for muscle tissue engineering (MTE), specifically in the context of cultivated meat applications. Through a comparative analysis between random and aligned CAN, utilizing C2C12 and H9c2 myoblasts, we unveil the unparalleled capabilities of random CAN in facilitating muscle differentiation, independent of differentiation media, by exploiting the YAP/TAZ-related mechanotransduction pathway. In addition, we have successfully developed a novel process for stacking cell-loaded CAN sheets, enabling the production of a three-dimensional meat product. C2C12 and H9c2 loaded CAN sheets were stacked (up to four layers) to form a ~300–400 μm thick tissue 2 cm in length, organized in a mesh of uniaxial aligned cells. To further demonstrate the effectiveness of this methodology for cultivated meat purposes, we have generated thick and viable constructs using chicken muscle satellite cells (cSCs) and random CAN. This groundbreaking discovery offers a cost-effective and biomimetic solution for cultivating and differentiating muscle cells, forging a crucial link between tissue engineering and the pursuit of sustainable and affordable cultivated meat production.